Hubungan Pengetahuan Mahasiswa tentang Siaga Bencana dengan Kesiapsiagaan dalam Menghadapi Bencana Banjir di STIKes RSPAD Gatot Soebroto - Wijayanti, Rina; Raidanti, Dina; Lestari, Septia Dwi (Jurnal Riset Hesti Medan, 2025)
Knowledge of disaster preparedness plays a crucial role in enhancing individuals’ readiness to face disasters, including floods. This study aims to analyze the relationship between university students’ knowledge of disaster preparedness and their level of readiness to face floods. The method used is a quantitative study with a descriptive-correlational approach. Data were collected through a questionnaire distributed to 200 students at a university in a flood-prone area. The results indicate that most students possess sufficient knowledge regarding disaster preparedness; however, their level of preparedness remains low, particularly in terms of physical preparation and emergency supplies. Correlation analysis indicates a significant positive relationship between students’ knowledge of disaster preparedness and their preparedness to face floods (p < 0.05). Based on these findings, it is recommended that disaster preparedness education programs be strengthened among students to improve their preparedness for flood disasters. This study is expected to provide insights for university administrators and relevant institutions in designing more effective disaster preparedness training and awareness programs.